EXAMINATION OF INTERNAL FACTORS IN TRAVEL AND TRAVEL DECISIONS (LITERATURE REVIEW) - Kalmar-Rimoczi, Csilla; Lenkovics, Beatrix (European Scientific Journal, ESJ, 2015)
Decisions made by people’s travelling are influenced by several internal and external factors. Consumer behaviour research has discovered many types of factors, the scope of which has been constantly widening in recent years and decades. Our decisions are influenced by the social group, the culture, the family. We obtain information from the social group, which has an impact on our consumer decisions. At the same time, consumer behaviour can be affected by the sex, age, marital status, and the life cycle as well. Internal factors include motivation, attitude and also personality. The object of this publication is intended literary summary, organization of piece of secondary sources of information. This study aims to present the internal factors that influence travel decisions. We used relevant Hungarian and international secondary sources in our work, which we are in thematically system and supplemented with our critical opinions.